Decentralized state feedback control of linear time-invariant system with free-interface substructures. (December 2021) - Liu, Gang; Jiang, Wei; Yang, Qingshan; Wang, Qi; Law, S.S.
Abstract: The state space model and local state controller of a conventional decentralized control system are based on the physical parameters or vibration modes of the whole structure. The interaction controllers between the isolated subsystems were usually ignored or they were formulated with the diagonal dominant theory. A new decentralized control method is proposed in this paper to address these disadvantages based on the free-interface substructures method. The stability of each isolated subsystem is ensured with the state space model, and the local state controllers of the open-loop subsystems are formulated from the substructural vibration modes. The interaction controller is derived from the interface forces between the coupling substructures. This ensures the stability of the close-loop whole system with no reference to the popular diagonal dominant theory. Numerical application to a six-storey plane frame under seismic excitation demonstrates that both the substructures and the whole structural system can have better control effects and stability compared to the conventional decentralized control method with more uniform and less demand on the performances of distributed dampers in the isolated subsystems.